Atypical DNA replication in Haloferax volcanii in the absence of replication origins - Smith, Victoria Emily (2022)
Replication origins are the sites of initiation of DNA replication. Origins are universal and have been assumed to be essential. However, the halophilic archaeon Haloferax volcanii is able to survive in the absence of origins, in fact growing faster than its wild-type counterpart. Replication in the absence of origins has been proposed to depend on replication-dependent replication (RDR), due to the requirement in the origin-deleted H. volcanii mutant for the recombinase protein, RadA.